2020
DOI: 10.1101/2020.02.07.937862
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe acute respiratory syndrome-related coronavirus: The species and its viruses – a statement of the Coronavirus Study Group

Abstract: AbstractThe present outbreak of lower respiratory tract infections, including respiratory distress syndrome, is the third spillover, in only two decades, of an animal coronavirus to humans resulting in a major epidemic. Here, the Coronavirus Study Group (CSG) of the International Committee on Taxonomy of Viruses, which is responsible for developing the official classification of viruses and taxa naming (taxonomy) of the Coronaviridae family, assessed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
1,233
1
118

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,583 publications
(1,423 citation statements)
references
References 42 publications
(13 reference statements)
9
1,233
1
118
Order By: Relevance
“…Subsequent virus isolation from human patients and molecular analysis showed that the pathogen was a new coronavirus (CoV), first named 2019-nCoV, and subsequently this disease was renamed by WHO as COVID- 19. A study group of the International Committee on Taxonomy of Viruses (ICTV) proposed the name SARS-CoV-2, but this name remains to be officially approved [1]. This new CoV is now the seventh member of the Coronaviridae known to infect humans.…”
Section: Emergence Of Covid-19mentioning
confidence: 99%
“…Subsequent virus isolation from human patients and molecular analysis showed that the pathogen was a new coronavirus (CoV), first named 2019-nCoV, and subsequently this disease was renamed by WHO as COVID- 19. A study group of the International Committee on Taxonomy of Viruses (ICTV) proposed the name SARS-CoV-2, but this name remains to be officially approved [1]. This new CoV is now the seventh member of the Coronaviridae known to infect humans.…”
Section: Emergence Of Covid-19mentioning
confidence: 99%
“…Since the emergence of the 2019 novel coronavirus (2019-nCoV) infection in Wuhan, China, in December 2019 [1] , it has rapidly spread across China and many other countries [2][3][4][5][6][7][8] . So far, 2019-nCoV has affected more than 43 0 0 0 patients in 28 countries/regions and has became a major global health concern ( https: //www.who.int/docs/default-source/coronaviruse/situation-reports/ 20200211-sitrep-22-ncov.pdf?sfvrsn=6f80d1b9 _ 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…On 11 February 2020, the World Health Organization (WHO) announced a new name for the epidemic disease caused by 2019-nCoV: coronavirus disease (COVID-19). Regarding the virus itself, the International Committee on Taxonomy of Viruses has renamed the previously provisionally named 2019-nCoV as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [3] .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of identifying the priming coronavirus, it is worthwhile looking at SARS-CoV as its introduction to humans has been suggested to have occurred in the Hubei Province [13]. The genetic sequence possesses numerous dissimilarities to the virus responsible for COVID-19, tentatively named SARS-CoV-2 [14], with approximately 79% homology [15]. For example, Hua et al [16] identified two specific epitopes on the SARS-CoV spike protein, 447e458 and 789e799.…”
Section: Introductionmentioning
confidence: 99%